FRI0384 Usefulness of Brain MRI in Early Lupus: How the Morphological Imaging Changes at Onset of the Disease and After Follow-Up. (9th June 2015) - Silvagni, E.; Bortoluzzi, A.; Padovan, M.; Furini, F.; Borrelli, M.; Govoni, M.
Abstract : Background: The prevalence of neuroimaging abnormalities is not defined in newly-diagnosed Systemic Lupus Erythematosus (SLE), especially in those patients without overt neuropsychiatric (NP) symptoms; furthermore the clinical significance of these alterations is not clear at all. Objectives: To assess the prevalence of brain abnormalities found by Magnetic Resonance Imaging (MRI) in a monocentric cohort of patients with early SLE onset (within 12 months from diagnosis) with (NP-SLE) or without NP manifestations (SLE) and to assess if early abnormal neuroimaging findings could have a predictive role for lesion load progression or the occurrence of subsequent NP events. Methods: We selected SLE patients, less than 55 years, diagnosed according to the 1997 ACR criteria, who underwent brain MRI examinations within 12 months since diagnosis and then repeated it in the following 24-36 months. Brain MRI results were considered as absence or presence of white matter hyperintensities (scoring 0-3 if focal lesions were respectively none, 1, 2-4 or >5) and also as absence or presence of atrophy (scoring 0-3 if atrophy was absent, light, moderate or severe) according to a modified semiquantitative scoring system proposed by Petri et al. Then we evaluated the appearance of each new NP event along a median follow up period of 42 months. Results: We retrospectively evaluated 752 patients referred consecutively at our clinic dedicated to SLE in a period of 20 years (between 1995 and 2014); 46 patients met the criteria for inclusion in the study. The mean age of the whole studied population was 34 years (14-55 yrs), 93.5% female. Of these patients, 28 had at least 1 NP event at time of diagnosis (61%). Overall an abnormal MRI was reported in 21 patients (46%), especially in those with NP involvement (18 NP-SLE and 3 SLE, p=0, 0023). At baseline median atrophy score and WMHI score were 0, 15 and 1, 02 respectively. After the first NP event all patients either increased their immunosuppressive therapy (steroid and/or cyclophosphamyde bolus) or added aspirin low dose or anticoagulant drugs. At the time of the second MRI, a lesion load progression or worsening was seen in 26% (12): 29% (8) of NPSLE and 22% (4) of SLE pts (p>0, 05); in all SLE patients the first MRI was negative. Total and median (1, 2) WMHI score worsened during FU, median score for atrophy doubled (0, 28). Almost all (92%) worsened MRI were associated with positivity of antiphospholipid antibodies. Comparing patients with unchanged MRI to those with worsened MRI a new NP event was recorded in 5 pts versus 6 pts (p=0, 02), for a total of 11 new NP episodes. Conclusions: Imaging abnormalities are present in a high percentage of SLE individuals at onset of disease (46%). A basal neuroimaging evaluation in young patients with newly diagnosed SLE is recommended especially because the evolution of the neuroradiological pictures seems to be independent of the previous history. Serial assessment is extremely useful to compare with any further imaging finding. Although a predictive value for abnormal neuroimaging in new appearance of NP event has yet to be demonstrated we found that MRI worsening could predict the occurrence of new NP event during follow up. Disclosure of Interest: None declared